Operationalizing One Health Employing Social-Ecological Systems Theory: Lessons From the Greater Mekong Sub-region - Wilcox, Bruce A.; Aguirre, A. Alonso; De Paula, Nicole; Siriaroonrat, Boripat; Echaubard, Pierre (Frontiers in Public Health, 2019)
The idea of the interdependency of the health of humans, animals, and ecosystems emerged from the interplay of theory and concepts from medicine, public health and ecology among leading thinkers in these fields during the last century. The rationale for One Health and its focus on the “human, animal, and environmental interface” stems from this legacy and points to transdisciplinary, ecological and complex systems approaches as central to One Health practice. Demonstration of One Health's efficacy, its wider adoption and continual improvement require explicit operational criteria and evaluation metrics on this basis. Social-Ecological Systems Theory with its unique conception of resilience (SESR) currently offers the most well-developed framework for understanding these approaches and development of performance standards. This paper describes operational criteria for One Health developed accordingly, including a protocol currently being tested for vector borne disease interventions. Wider adoption of One Health is most likely to occur as One Health practitioners gain an increasing familiarity with ecological and complex systems concepts in practice employing a transdisciplinary process. Two areas in which this inevitably will be required for significant further progress, and where the beginnings of a foundation for building upon exist, include: (1) Emerging and re-emerging zoonotic diseases, and (2) successful implementation of the United Nations (UN) Sustainable Development Goals (SDGs). The former includes the challenge of stemming the threat of new microbial pathogens, anti-microbial resistant variants of existing pathogens, as well as resurgence of malaria and other recalcitrant diseases. The applicability of SESR in this regard is illustrated with two case examples from the Greater Mekong Subregion, Avian Influenza (H5N1) and Liver Fluke (Opisthorchis viverrini). Each is shown to represent a science and policy challenge suggestive of an avoidable social-ecological system pathology that similarly has challenged sustainable development. Thus, SESR framing arguably is highly applicable to the SDGs, which, to a large extent, require consideration of human-animal-environmental health linkages. Further elaboration of these One Health operational criteria and metrics could contribute to the achievement of many of the SDGs.